Unbounded Organisation and the Future of Socialism - Richards, H (TAYLOR & FRANCIS LTD, 2013)
This article starts with the question whether the socialism Neville Alexander advocated is a thing of the past or a prospect for the future. It considers two forms of 20th-century socialism, the centrally planned economy and social democracy, in the light of Marx s concept of accumulation. Accumulation names both the logic of capitalism and the dynamic that drives it. A focus on the need to deal with the probability that the accumulation dynamic will falter in the process of moving from capitalism to socialism helps to explain socialism s decline. Unbounded organisation is introduced as a broader concept that includes the bounded social organisation that frames capitalism and its accumulation dynamic as a special case. It helps to both explain the decline of socialism and to suggest how to reverse that decline. It is suggested that the socialism of the future can best be defined not as a certain form of social organisation, but rather as the power of the people to choose the set of economic and other institutions that works best for them. Three of Alexander s contributions to building an unbounded socialism are found in his proposals for grass-roots organising at the neighbourhood level, in his promotion of multilingualism, and in his advocacy of alternative education. © 2013 Copyright The University of Johannesburg.